Pre‐harvest methyl jasmonate treatments increase antioxidant systems in lemon fruit without affecting yield or other fruit quality parameters. (16th May 2019) - Serna‐Escolano, Vicente; Valverde, Juan M; García‐Pastor, María E; Valero, Daniel; Castillo, Salvador; Guillén, Fabián; Martínez‐Romero, Domingo; Zapata, Pedro J; Serrano, Maria
Abstract: BACKGROUND: Jasmonic acid (JA) and its volatile derivative methyl jasmonate (MeJA) are hormones involved in the regulation of many processes in plants and act (when applied as a post‐ or pre‐harvest treatment) to increase fruit bioactive compounds with antioxidant potential. However, there is no literature available regarding the effect of pre‐harvest MeJA treatment on lemon fruit antioxidant systems, which was the aim of the present study. RESULTS: MeJA treatment (0.1, 0.5 and 1.0 mmol L –1 ) increased antioxidant compounds, such as phenolics, in the juice and flavedo of 'Fino' and 'Verna' lemons at harvest, with the most effective concentration being 0.1 mmol L –1 in both cultivars. In addition, catalase (CAT), peroxidase (POD) and ascorbate peroxidase (APX) activities were also increased by MeJA treatment, with the highest increases being also found with 0.1 mmol L –1 . The increases in APX and CAT were maintained from one treatment to another during fruit development on the tree, whereas the increase on POD disappeared after 8–10 days of each treatment. For both antioxidant systems, the highest increases were found in lemon harvested at the commercial ripening stage. By contrast, crop yield, fruit ripening process and quality parameters were generally not affected by MeJA treatment. CONCLUSION: Preharvest MeJA treatment could be a useful tool for increasing antioxidant potential and the health beneficial effects of lemon fruit consumption, given the relationship between these properties and phenolic content. Moreover, the increased concentration of phenolics and the activity of antioxidant enzymes in the flavedo of MeJA treated fruit could increase lemon tolerance to chilling injury and decay during postharvest storage. © 2019 Society of Chemical Industry